Can Institutional Ownership Moderate The Influence of Deferred Taxes and Tax Planning on Earnings Management? Evidence from Indonesia - Raden Arief Wibowo (Profesional Muda Cendekia Publishing, 2020)
This research aims to examine the effect of deferred tax expense, tax planning, managerial ownership on earnings management which is moderated by institutional ownership in manufacturing companies in the indonesia stock exchange in 2015-2018. The research sample was 16 companies. The sampling technique in the research used the purposive sampling method. This research uses multiple linear regression analysis and Moderated Regression Analysis (MRA) with the help of the IBM SPSS 24 program. The results of this study indicate that simultaneously the variables of defererred tax expense, tax planning, managerial ownership affect earnings management. Whereas partially deffered tax expense affect earnings management, tax planning and managerial ownership do not affect earnings management. Institusional ownership is able to influence (weaken) the relationship between deffered tax expense on earnings management, institusional ownership is able to influence (strengthen) the relationship between managerial ownership on earnings management, but institusional ownership is not able to influence the relationship between tax planning on earnings management